Pengaruh Kualitas Produk, Minat Beli dan Perilaku Konsumen Terhadap Keputusan Pembelian di Minimarket Victoria Tiban - Novianti Novianti; Asron Saputra (Komunitas Dosen Indonesia, 2023)
A factors can lead more competitors, technology and education related to marketing, can increase speed and stimulate business owners in realizing innovations that can develop and manage their business meeting the needs of consumers. Product quality activities, purchase intention and consumer behavior influenced consumers on purchasing decisions. The aims of that studies is determining effects of product quality, purchase intention and consumer behavior on purchasing decisions at Victoria Tiban Minimarket. This researches are conducte use quantitative techniques. The researches sample used was 357 respondents are use as data collection techniques. By using SPSS 25 software, analysis techniques include descriptive statistical, data quality, classical assumption, influence, and hypothesis testing. Based on the results, product quality, purchase intention, and consumer behavior influence purchasing decisions by 46.1%. It was found that product quality, purchase intention, and consumer behavior had a positive and significant effect partially or simultaneously on purchasing decisions at Victoria Tiban Minimarket.